Kurikulum PPKN Berorientasi Critical Thinking dalam Pembentukan Warga Negara Demokratis: Studi Pustaka - Budi Azhari Muda Hasibuan; Mora Rizky Adhawiyah; Alya Royani; Heri Yanto Zega (Al-Riwayah : Jurnal Kependidikan, 2026)
The Citizenship Education (PPKn) curriculum plays a strategic role in shaping democratic citizens amidst the challenges of the 21st century. This study aims to examine the implementation of a PPKn curriculum oriented toward developing critical thinking skills as a primary instrument in fostering democratic character. Using a literature review approach, this research analyzes the concepts of the democratic citizen, the essence and functions of Citizenship Education, and the urgency of integrating critical thinking into the curriculum. The results indicate that a critical thinking orientation in Citizenship Education requires humanistic, dialogical, and reflective learning models and strategies. Systematic and adaptive lesson planning serves as a crucial foundation for integrating these skills into the learning process. The implications of implementing this curriculum not only enhance students' analytical acumen regarding social issues but also strengthen the active participation and responsibility of learners as democratic citizens. Thus, strengthening critical thinking skills within Citizenship Education is an essential step in cultivating a generation capable of navigating the dynamics of social change with wisdom